Esthetic rehabilitation for premature loss of primary anterior teeth - Paridhee Jalan; Aindrila Ghosh; Shabnam Zahir; Gautam Kumar Kundu (Wolters Kluwer Medknow Publications, 2019)
Over years primary anterior teeth have been prematurely lost due to Early Childhood Caries and trauma. While in the past once lost primary teeth could not be replaced, now due to increased aesthetic demands of the patient and their family, different fixed functional space maintainers have come to the forefront for aesthetically rehabilitating prematurely loss deciduous anterior teeth. This case report discusses how an avulsed deciduous maxillary anterior teeth was replaced in a three and a half year old male patient using a fixed functional space maintainer.